The Impact of School Principal Leadership and Teacher Work Behavior on Improving the Quality of Graduates at Junior High School, Percut Sei Tuan - Saimun Saimun; Saima Rambe (Jurnal Mantik, 2022)
Education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential. The purpose of this study was to determine the effect of principal's leadership, teacher's work behavior on improving the quality of graduates in SMP Negeri in Percut Sei Tuan district. This research is a descriptive study which was conducted in a public junior high school in the district of Percut Sei Tuan, Deli Serdang Regency, North Sumatra. The sample is 77. The analysis of the research results uses descriptive statistics, product moment correlations, and multiple linear correlations. The results of the hypothesis test show that: there is a positive and significant influence between the principal's leadership on the quality of graduates at the State Junior High School in Percut Sei Tuan district by 31.3%; there is a positive and significant influence between the work behavior of teachers on the quality of graduates in SMP Negeri in Percut Sei Tuan district by 34.1%; and there is a positive and significant effect together of 43.9%.